EFFORTS TO IMPROVE SCIENCE LEARNING OUTCOMES THROUGH THE DISCOVERY LEARNING MODEL ASSISTED BY INTERACTIVE MEDIA FOR SEVENTH-GRADE STUDENTS AT SMP NEGERI 2 PANGKAJENE - Taufiqurrahman Taufiqurrahman; Arie Arma Arsyad; Sukmawanty Rahman; Saparuddin Saparuddin (Jurnal Pembelajaran Sains, 2023)
This research is based on the learning model traditionally applied to grade 7 science learning. The low mastery of science learning outcomes for the students of class VII Ibnu Batuta SMPN 2 Pangkajene. The purpose of this study was to see: (1) improve the presentation of mastery learning outcomes using Discovery Learning-based learning models assisted by interactive media, (2) improve learning outcomes using Discovery Learning-based learning models assisted by interactive media. Research method The technique used is Collaborative Classroom Action Research (PTKK). The data collection technique is based on the results of learning tests and observation sheets on the implementation of the learning model. The results showed that (1) the percentage of classical completeness increased from 16.12% in the very low category before the cycle, 48.39% in the low category in the first cycle and 96.67% in the very high category in the second cycle; (2) the category of increasing learning outcomes of class VII Science students at Ibnu Batuta SMPN 2 Pangkajene has increased from 0.37 in the moderate category to 0.68 in the moderate category with an increase of 0.31 in the medium category.